Intergenerational transmission of values in Polish families in the Second Republic in the context of educational ideology of the state in years 1918–1939 - Samsel, Agata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The intergenerational transmission of values is an indispensable condition of the continuity of a culture, and thus it guarantees the survival of the group. Entering theworld of values is inherent in the education of the young generation. The oldest and most important educational environment is the family, where the child’s personality isshaped and its identity is created. As a result of the intergenerational transmission of values the child acquires knowledge, which is the sum of the experience of previousgenerations. In addition to acquiring the ability to distinguish good from evil, and learning the basic principles and standards governing relationships, the child assimilatesa number of elements that make up the culture – language, history, tradition, beliefs, symbols of religious and national customs and habits.
Keywords: family; education; values; culture; The Second Republic of Poland